Constitutive β-catenin signaling by the viral chemokine receptor US28. - Ellen V Langemeijer (Public Library of Science (PLoS), 2012)
Chronic activation of Wnt/β-catenin signaling is found in a variety of human malignancies including melanoma, colorectal and hepatocellular carcinomas. Interestingly, expression of the HCMV-encoded chemokine receptor US28 in intestinal epithelial cells promotes intestinal neoplasia in transgenic mice, which is associated with increased nuclear accumulation of β-catenin. In this study we show that this viral receptor constitutively activates β-catenin and enhances β-catenin-dependent transcription. Our data illustrate that this viral receptor does not activate β-catenin via the classical Wnt/Frizzled signaling pathway. Analysis of US28 mediated signaling indicates the involvement of the Rho-Rho kinase (ROCK) pathway in the activation of β-catenin. Moreover, cells infected with HCMV show significant increases in β-catenin stabilization and signaling, which is mediated to a large extent by expression of US28. The modulation of the β-catenin signal transduction pathway by a viral chemokine receptor provides alternative regulation of this pathway, with potential relevance for the development of colon cancer and virus-associated diseases.